Assessing employee creativity and innovation in organization: development of measuring item / Nabila Huda Ibrahim, Tuan Nooriani Tuan Ismail and Mahadir Ladisma @ Awis - Ibrahim, Nabila Huda; TTuan Ismail, Tuan Nooriani; Ladisma @ Awis, Mahadir (Journal of Administrative Science, 2018)
Producing novel and useful ideas are demands for every organization to achieve competitive advantages that could guarantee the organizational survival. Creativity and innovation indicates the ability of employees to produce and implement novel ideas in the organization. Creativity and innovation may be nurtured in the organization through engagement, leadership and environment in organization. Creativity and innovation is an intangible skills and irreplaceable talents that needs to be secured in every organization. In order to gain employee creativity and innovation, employee needs to be engaged towards creativity and innovation activities. Assesement towards creativity and innovation is necessary to identity the level of employee creativity and innovation as well as for improving the level. In assessing the employee creativity and innovation in organization, and appropriate measurement is necessary. This paper is intended to build the measuring items for employee to assess their own creativity and innovation. The main focus of this paper is to discuss the development items in measuring employee creativity and innovation. Three factors of personal assessment, role of top management and organization environment are the dimension for assessing employee creativity and innovation. These three factors are significant for engaging employees towards creativity and innovation. This measurement should be employed in every organization as a form to assess employee creativity and innovation.